Analyzing Viewer Engagement with Historical Content on YouTube: Insights from Perjalanan Jalur Rempah Nusantara - Ramli, Arwin; Abdull Rahman, Zainatul Shuhaida (Swarnadwipa, 2024)
In the digital era, historical education has evolved from traditional methods to embrace digital platforms like YouTube, revolutionizing public engagement with historical narratives. This study investigates viewer interactions with historical content on YouTube by analyzing comments on the video Perjalanan Jalur Rempah Nusantara. Through thematic analysis, four primary themes were identified: visual and narrative quality, historical accuracy, educational value, and personal connections. These findings highlight the importance of well-produced, accurate, and educationally valuable content that resonates personally with viewers. The insights derived provide valuable guidelines for educators and content creators aiming to enhance digital history education.